2005
DOI: 10.1017/s0140525x05000051
|View full text |Cite
|
Sign up to set email alerts
|

Sociosexuality from Argentina to Zimbabwe: A 48-nation study of sex, culture, and strategies of human mating

Abstract: The Sociosexual Orientation Inventory (SOI; Simpson & Gangestad 1991) is a self-report measure of individual differences in human mating strategies. Low SOI scores signify that a person is sociosexually restricted, or follows a more monogamous mating strategy. High SOI scores indicate that an individual is unrestricted, or has a more promiscuous mating strategy. As part of the International Sexuality Description Project (ISDP), the SOI was translated from English into 25 additional languages and administer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

53
729
10
59

Year Published

2009
2009
2016
2016

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 819 publications
(851 citation statements)
references
References 310 publications
(349 reference statements)
53
729
10
59
Order By: Relevance
“…A more recent example comes from Colombia, where high male mortality rates, yielding an abundance of women in some regions, are associated with decreased marriage rates and higher proportions of men in concurrent relationships [35]. Cross-cultural research corroborates this pattern, revealing female-biased sex ratios associated with lower levels of male parental investment and higher rates of femaleheaded households [36]. Indeed, when there are too many men, the nature of relationships change.…”
Section: Box 1 Changing the Direction Of The Causal Arrow Between Pimentioning
confidence: 99%
See 1 more Smart Citation
“…A more recent example comes from Colombia, where high male mortality rates, yielding an abundance of women in some regions, are associated with decreased marriage rates and higher proportions of men in concurrent relationships [35]. Cross-cultural research corroborates this pattern, revealing female-biased sex ratios associated with lower levels of male parental investment and higher rates of femaleheaded households [36]. Indeed, when there are too many men, the nature of relationships change.…”
Section: Box 1 Changing the Direction Of The Causal Arrow Between Pimentioning
confidence: 99%
“…For example, Angrist found that, among immigrants to the USA, high sex ratios had a large positive effect on the likelihood of female marriage and a large negative effect on female labor force participation; with men providing investment, women could avoid wage labor [37]. In general, malebiased sex ratios are associated with a greater proportion of males being married [34,38], less promiscuity in both sexes [36,39,40], and greater conjugal stability [41], all of which might contribute to the lower I s values for men shown in Box 2.…”
Section: Box 1 Changing the Direction Of The Causal Arrow Between Pimentioning
confidence: 99%
“…1 Men's and women's mean level of physical attraction to the opposite-sex friend they were with when they were approached in men's and women's mating adaptations might influence how they think about friends. For example, men's stronger orientation toward short-term mating relative to women's (Buss and Schmitt 1993;Schmitt 2005) corresponds with differences in how the sexes select and feel about their oppositesex friends. Men more than women view sexual attraction as a benefit of opposite-sex friendships (Bleske and Buss 2000), and men more than women desire (Bleske-Rechek and Buss 2001) and prioritize (Lewis et al 2011(Lewis et al , 2012 attractiveness in an opposite-sex friend.…”
Section: Resultsmentioning
confidence: 99%
“…Entre as hipóteses mais testadas, Confer et al (2010) defendem os mecanismos que lidam com "aproveitadores" em grupos cooperativos, trapaceiros, localização espacial feminina e outros, como as preferências e estratégias no relacionamento (Buss, 2007) e, também, as estratégias de cópula (Schmitt, 2005).…”
Section: Psicologia Evolutivaunclassified